The Coevolution of Industries and Important Features of Their Environments - Murmann, Johann Peter (Organization Science, 2013)
As the rate of innovation increases, organizational environments are becoming faster and more complex, posing greater challenges for organizations to adapt. This study argues that the concept of coevolution offers a bridge between the prescient adaptationist and ex post selectionist perspectives of organizational change to account for the increasing rates of change. The mutual causal influences in a coevolutionary relationship help explain why competing sets of firms or individual firms can capture dominant shares in product markets. Using a comparative historical method and drawing on evidence from five countries over a 60-year period, this paper inquires how precisely coevolutionary processes work in shaping the evolution of industries and important features of their environments. It identifies—in the context of the synthetic dye industry—three causal mechanisms (exchange of personnel, commercial ties, and lobbying) and suggests how they acted as levers on the fundamental mechanisms of evolution. Understanding the levers is important for managing change in a world that is increasingly becoming coevolutionary, requiring managers to focus more on the emergent, system-level properties of their environments.